The Relationship between the Intensity of Cadre Assistance and Compliance with Iron Supplement Consumption among Pregnant Women at the Tomalou Community Health Center, Tidore Kepulauan City - Juliyana Maradjabessy; Reny Retnaningsih (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Anemia during pregnancy is a public health issue that remains a challenge in developing countries, including Indonesia. Iron tablets are recommended as the primary intervention to prevent anemia, but compliance among pregnant women in taking iron tablets varies and is influenced by various factors, including health worker counseling. This study aims to analyze the relationship between the intensity of cadre assistance and the level of compliance with TTD consumption among pregnant women at the Tomalou Community Health Center, Tidore Kepulauan City. The study design used an observational analytical approach with a cross-sectional method. The study sample consisted of 30 pregnant women selected using total sampling technique. The independent variable was the intensity of cadre assistance, while the dependent variable was the level of compliance with TTD consumption. Data were collected using observation sheets, consumption monitoring forms, and respondent identity questionnaires, then analyzed using Spearman's rank correlation test at a significance level of 0.05. The results showed that most respondents were compliant in consuming TTD, but there was no significant relationship between the intensity of cadre assistance and the level of compliance with TTD consumption (r = 0.036; p = 0.848). This study concluded that the frequency of assistance alone was not sufficient to influence TTD consumption compliance, thus requiring a more comprehensive, educational assistance approach that involved family support. These findings could form the basis for evaluating the cadre assistance program in preventing anemia in pregnant women.